123 Acceptability of the Ambient Intelligent Geriatric Management (AMBIGEM) System: A Technological Solution to Prevent in-Patient Falls. (20th December 2019) - Dollard, Joanne; Visvanathan, Renuka; Hill, Keith; Ranasinghe, Damith; Lange, Kylie; Jones, Katherine; Boyle, Eileen; Zhou, Adele; Ng, Nicholas; Wilson, Anne
Abstract: AmbIGeM is a technological solution to prevent in-patient falls in patients aged >65. It has been evaluated in a 100-week stepped wedge pragmatic design in two geriatric evaluation and management (GEM) wards and a general medical ward in two Australian hospitals (Visvanathan, Ranasinghe, Wilson et al., Injury Prevention, 2017, 0:1). Evaluation of acceptability of the AmbIGeM system from the perspectives of patients and staff who experienced it is reported here. 30 patients completed a 24-item survey, 27 patients were interviewed, 22 staff participated in 3 focus groups and 51 staff completed a 39-item survey. Survey data were descriptively analysed, and focus group and interview data were thematically analysed. In patient surveys, patients were overall strongly positive, with means 8+ (on 11-point scale) on most items. In patient interviews, the AmbIGeM system was considered a good idea to prevent falls. Most patients thought the singlets comfortable and had no concerns for their privacy nor impact on normal activity. Patients and families felt reassured, although sometimes they misunderstood the purpose of AmbIGeM. In staff focus groups, staff perceived AmbIGeM beneficial in that it can detect and alert movement in patients who require supervision. In both GEM wards, AmbIGeM was considered particularly beneficial, practical and valuable to use on night shift. Factors such as perceived technical limitations (false and delayed alerts) and felt staff burden impacted on acceptability. In staff surveys, 56% agreed/strongly agreed that AmbIGeM has the capability to prevent falls while 16% disagreed/strongly disagreed, 62% thought AmbIGeM would be more user friendly if it was consistently accurate and 76% believed that AmbIGeM takes a moderate/lot of extra work. Conclusion: AmbIGeM is largely acceptable to patients and requires further refinement for staff. Feedback is valuable to further refine the system.